DEVELOPING STUDENTS’ COMPOSITIONAL THINKING THROUGH DIGITAL AND INNOVATIVE TECHNOLOGIES - Jalolov Shavkat Choriyevich (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Abstract: This article explores the role of digital and innovative technologies in fostering students’ compositional thinking in art education. It emphasizes how project-based learning, flipped classrooms, virtual design tools, and interactive digital platforms enhance creative problem-solving, artistic competencies, and analytical reasoning. The study refers to Shovdirov S.A. and other scholarly research to provide practical and theoretical perspectives on implementing innovative approaches in art classrooms.